2013
DOI: 10.1128/aac.02622-12
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum β-Lactamase CTX-M-15-Producing Klebsiella pneumoniae of Sequence Type ST274 in Companion Animals

Abstract: Screening of extended-spectrum ␤-lactamase (ESBL)-producing Gram-negative bacteria in companion animals living in the Paris area in France identified a high rate of CTX-M-15-producing Klebsiella pneumoniae. Those isolates were recovered during the 2010-2011 period from both infections and asymptomatic colonizations. Sequence typing revealed that most of these isolates belonged to sequence type ST274. Interestingly, the bla CTX-M-15 gene was located on a specific and novel plasmid scaffold. These findings highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 22 publications
6
47
3
Order By: Relevance
“…The highest E. coli isolation prevalence (40.7%) recorded in this study differs from the result of a similar study conducted in Enugu State, Nigeria, in which Klebsiella was the dominant (67.4% isolation prevalence) enterobacteria genus isolated from healthy pigs . The result of this study, also contrasted Poirel et al (2013) who reported Klebsiella, with 51.5% prevalence, as the dominant genus among 33 ESBLproducing enterobacterial isolates from dogs/cats/others in France.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…The highest E. coli isolation prevalence (40.7%) recorded in this study differs from the result of a similar study conducted in Enugu State, Nigeria, in which Klebsiella was the dominant (67.4% isolation prevalence) enterobacteria genus isolated from healthy pigs . The result of this study, also contrasted Poirel et al (2013) who reported Klebsiella, with 51.5% prevalence, as the dominant genus among 33 ESBLproducing enterobacterial isolates from dogs/cats/others in France.…”
Section: Discussioncontrasting
confidence: 56%
“…An Iranian study also reported lower ESBL-producing E. coli isolation prevalence in faecal samples of healthy cats (Akhtardanesh et al, 2015). The E. coli isolation prevalence in the present study, is however, lower than ESBL-producing E. coli isolation prevalence recorded among 20 faecal ESBL-producing enterobacterial isolates from healthy dogs/cats in Romania (Cozma et al, 2015b), 63 faecal E. coli isolates from hospitalized dogs in South Korea (So et al, 2012), 33 ESBL-producing enterobacterial isolates from companion animals in France (Poirel et al, 2013), 15 E. coli isolates from urine samples of 138 sick cats in Italy (Nebia et al, 2014) and in faecal samples of 20 each of healthy and diarrhoeic dogs in the Netherlands (Hordjik et al, 2013), respectively. It is also lower than 62% ESBL-resistant E. coli isolation prevalence in faecal samples from 13 sick dogs reported by Damborg et al (2011) in Denmark.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations